When Partial Hospitalization Fails: Risk Factors for Inpatient Hospitalization. Issue 6 (June 2016) - Beard, Courtney; Hearon, Bridget A.; Lee, Josephine; Kopeski, Lynne M.; Busch, Alisa B.; Björgvinsson, Thröstur
Abstract : Abstract: Partial hospitalization is an understudied bridge between outpatient and inpatient care. One of its primary functions is to prevent the need for inpatient hospitalization. We examined potential demographic and clinical risk factors for inpatient hospitalization for current partial hospital patients. We conducted separate multiple logistic regression analyses for patients referred from inpatient care and the community. For individuals referred from inpatient care, suicidal ideation and greater psychotic symptoms upon admission to the partial program were associated with acute inpatient re-hospitalization. For individuals referred from the community, suicidal ideation and worse relationship functioning upon partial hospital admission were significant risk factors for inpatient hospitalization. Number of previous inpatient hospitalizations and greater substance abuse were not associated with inpatient hospitalization in either sample. Implications at the provider and program level are discussed.